Bandpass filter based on complementary split ring resonators at X-band - Furqan Furqan; Said Attamimi; Andi Adriansyah; Mudrik Alaydrus (Institute of Advanced Engineering and Science, 2019)
Complementary Split Ring Resonators were used integrated in a substrate integrated waveguide to generate passband charateristics in X-Band. Based on a parameter study with an electromagnetic commercial software, the characteristics of double and quadruple CSRRs according the reflection and transmission factor were observed. The computer simulation showed, the bandpass filter worked in the frequency range 8.12-8.63 GHz and 8.11-8.63 GHz for double and quadruple CSRR, respectively. The insertion loss was 0.12 dB and 0.015 dB. The measurement mit a vector network analyzer verified the simulation results. The frequeny range measured was 8.12-8.67 GHz and 8.12-8.61 GHz for double and quadruple CSRRs, respectively. The measured insertion loss was 0.25 dB and 0.2 dB.